Theoretical study of the electronic spectra of small molecules that incorporate analogues of the copper-cysteine bond - Do, Hainam; Besley, Nicholas A. (American Chemical Society, 2012)
The copper-sulphur bond which binds cysteinate to the metal centre is a key factor in the spectroscopy of blue copper proteins. We present theoretical calculations describing the electronically excited states of small molecules, including CuSH, CuSCH_3, (CH_3)_2SCuSH, (imidazole)-CuSH and (imidazole)_2-CuSH, derived from the active site of blue copper proteins that contain the copper-sulphur bond in order to identify small molecular systems that have electronic structure that is analogous to the active site of the proteins. Both neutral and cationic forms are studied, since these represent the reduced and oxidised forms of the protein, respectively. For CuSH and CuSH^+, excitation energies from time-dependent density functional theory with the B97-1 exchange-correlation functional agree well with the available experimental data and multireference configuration interaction calculations. For the positive ions, the singly occupied molecular orbital is formed from an antibonding combination of a 3d orbital on copper and a 3pπ orbital on sulphur, which is analogous to the protein. This leads several of the molecules to have qualitatively similar electronic spectra to the proteins. For the neutral molecules, changes in the nature of the low lying virtual orbitals leads the predicted electronic spectra to vary substantially between the different molecules. In particular, addition of a ligand bonded directly to copper results in the low-lying excited states observed in CuSH and CuSCH_33 to be absent or shifted to higher energies.